2013
DOI: 10.1088/0964-1726/22/10/104002
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar cross-linkers for PDMS networks with enhanced dielectric permittivity and low dielectric loss

Abstract: Dipole grafted cross-linkers were utilized to prepare polydimethylsiloxane (PDMS) elastomers with various chain lengths and with various concentrations of functional cross-linker. The grafted cross-linkers were prepared by reaction of two alkyne-functional dipoles, 1-ethynyl-4-nitrobenzene and 3-(4-((4-nitrophenyl)diazenyl)phenoxy)-prop-1-yn-1-ylium, with a synthesized silicone compatible azide-functional cross-linker by click chemistry. The thermal, mechanical and electromechanical properties were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…A more sophisticated method of increasing the permittivity has been presented by Madsen et al, who covalently linked high-dielectric constant dipolar molecules to the elastomer backbone via a novel type of chain extender. [18,19] Nevertheless, none of the reported elastomers presently meets the requirements that are foreseen for a highly efficient, reliable and thus also commercially attractive dielectric elastomer. The indisputable need for materials improvement leads to many unconventional approaches for reaching a breakthrough in the development of dielectric elastomer actuators.…”
Section: Introductionmentioning
confidence: 99%
“…A more sophisticated method of increasing the permittivity has been presented by Madsen et al, who covalently linked high-dielectric constant dipolar molecules to the elastomer backbone via a novel type of chain extender. [18,19] Nevertheless, none of the reported elastomers presently meets the requirements that are foreseen for a highly efficient, reliable and thus also commercially attractive dielectric elastomer. The indisputable need for materials improvement leads to many unconventional approaches for reaching a breakthrough in the development of dielectric elastomer actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Several promising materials have been developed based on silicone elastomers, and approaches are currently limited to two categories of elastomers, namely 1) composites with semiconductive metal oxides or screened conductive particles and 2) molecular modified elastomers. [2,3,4]. We here explore the most common approach of composites with high permittivity metal oxides as this method by far results in the cheapest elastomers due to the relatively low cost of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We here explore the most common approach of composites with high permittivity metal oxides as this method by far results in the cheapest elastomers due to the relatively low cost of e.g. TiO 2 and the ease of processing.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing attention is also attracted towards grafting of polar molecules onto the silicone polymer backbone which significantly improves the dielectric permittivity without compromising its high inherent breakdown strength and increasing dielectric loss [4]. It was also reported that grafting of less than 0.5 wt.% of push-pull dipols onto a crosslinker of the silicones can enhance the dielectric constant by 19% [5,6].…”
Section: Introductionmentioning
confidence: 99%